Disability and American Philosophies. - Whelan-Jackson, Nate; Brunson, Daniel J. ([Place of publication not identified] : Routledge, 2022)
Given basic commitments to philosophize from lived experience and a shared underlying meliorist impulse, American philosophical traditions seem well-suited to develop nascent philosophical engagement with disability studies. To date, however, there have been few efforts to facilitate research at the intersections of American philosophy and disability studies. This volume of essays seeks to offer some directions for propelling this inquiry. Scholars working in pragmatist and other American traditions consider intersections between American philosophy and work in disability studies. Consisting of three broader sections, one set of essays considers how American philosophies from contemporary Mexican philosophy to classical American pragmatism inform descriptions of disability and efforts at liberation. The next offer accounts of how American philosophies disclose alternative conceptions of epistemic and ethical issues surrounding disability. Finally, a section considers "living issues" of disability, including essays on parenting, immigration policy, and art education. Throughout, these works provide direction and orientation for further investigation at the intersection of American philosophies and disability studies.
Introduction: Disability and American PhilosophiesNate Whelan-Jackson & Daniel J. Brunson1. Collective Inferiority Complex as Disability: Samuel Ramos' Analysis of the Mexican PsycheSergio Gallegos2. Deweyan Tools for Disability Studies: Methodological Pluralism and Melioration of SufferingJustin Bell3. Pragmatic Individualism and the (Re)Production of DisabilityNate Whelan-Jackson4. Pragmatism and NeurodiversityDaniel J. Brunson5. Lost (And Lonely) in Translation: Dyslexia and Epistemic LonelinessKara Barnette6. Just Like an Animal: Cognitively Disabled Humans and the Argument from Marginal CasesTodd Lekan7. The Art of Interdependence: Autonomy, Heteronomy, and Social Support in Shannon Jackson's Criticism of Contemporary Art Social PracticesJohn Giordano8. Dewey on Disability and Epistemic VirtueSarah Woolwine 9. Gloria E. Anzaldúa and Crip Futurity in the AmericasAndrea Pitts10. The Right to Heal: Politics, Civil Rights, and the Need for New Ethical Concepts Regarding Regenerative Medical Care in OrthopedicsTommy Curry11. Stoic Pragmatism for Parenting a Child with Disabilities: An Essay Addressing Philosophers, Parents, Teachers, and Educational PolicymakersEric T. Weber
Keywords: Philosophy, American; Disabilities; PHILOSOPHY / General; PHILOSOPHY / Movements / Pragmatism